CONVERSION COSTS AND PRODUCTION COSTS BASED ON TIME-DRIVEN ACTIVITY-BASED COSTING AT PT SC GRESIK - Tamayo di Vaio Sanjaya (Research In Management and Accounting (RIMA), 2024)
The business world today has developments that can be said to continue to change over time, as indicated by tighter competition. In 2019, the COVID-19 pandemic also impacted many companies due to a decline in sales. This condition demands that business owners continue thinking about strategies and appropriately make various company decisions. What can be done, especially in manufacturing companies, is to increase the quality of the product as best as possible and sell it at an affordable price. This research aimed to calculate the cost of production (especially in analyzing conversion costs) using the Time-Driven Activity-based Costing (TDABC) System method at PT SC Gresik, East Java, Indonesia. It compared gross profit results from the Functional Based Costing (FBC) and TDABC System methods. This type of research is a case study. The research results show that the TDABC method's calculations are more precise than the FBC method. HJ 5 tons, HJ 8 tons, HJ 10 tons, and HJ 20 tons of products produce lower production costs and higher gross profits. The 2-ton HJ product produces a higher production cost and a lower gross profit when compared to the FBC method calculation. The TDABC method allocates costs based on the activity's time.